Effect of Counseling Approach and Learning Achievement to Moral Intelligence - Aisyah Aisyah (JETL (Journal of Education, Teaching and Learning), 2018)
This research aimed to know the effects the Rational Emotive Therapy (RET) with counseling approach and learning achievement toward the moral intelligence. This research used the experimental method and applied kinds of treatment, namely: RET counseling approach and Client-Centered Therapy (CCT) counseling approach. Each treatment involved two groups of students from Elementary School Students at Cipondoh 3 Tangerang Banten. The data analysis used in this research was two-way analysis of variance.The findings acquired was the differences between the moral intelligence of students who were counseled with RET counseling approach and CCT counseling approach. The group of students with slow learning achievement, the moral intelligence of those who were counseled with RET counseling approach was higher than those who were counseled with CCT counseling approach. For the group of students with high learning achievement, the moral intelligence of those who were counseled with RET counseling approach was lower than those who were counseled with CCT counseling approach. The results of this research indicate that counseling approaches can be used as a method to develop the moral intelligence of students.